Update on risankizumab for the treatment of moderate to severe psoriasis. (1st November 2020) - Al-Janabi, A; Warren, RB
ABSTRACT: Introduction: The therapeutic landscape for psoriasis is ever-changing. Risankizumab is the newest approved biologic and one of three currently licensed that targets the p19 subunit of interleukin-23 (IL-23). It is increasingly clear that different biologics vary in their efficacy, effectiveness, and safety profiles, highlighting that there is a need to understand for which patients and in which circumstances to use each drug. Areas covered: This article summarizes original clinical trial data, and reviews in more detail recent post-marketing studies and meta-analyses that differentiate risankizumab from other biologics. It also briefly explores the evidence for risankizumab in the treatment of other immune-mediated inflammatory diseases. Expert opinion: Risankizumab is a highly effective biologic for the treatment of moderate-to-severe plaque psoriasis. Recent open-label extension data for risankizumab shows sustained treatment responses to week 136. Indirect comparisons suggest IL-17 inhibitors have a faster onset, though head-to-head comparison with secukinumab shows non-inferiority at week 16 and superiority of risankizumab at week 52. Risankizumab is very well tolerated and data from the IMMhance trial suggests that risankizumab can be used in patients with latent tuberculosis without risk of reactivation.